GREEN TOURISM EXPERIENCE PADA SANGGRALOKA FARM DI DESA BRESELA, GIANYAR - Ni Nyoman Tri Anggreni; Ni Made Ary Widiastini; AA Ngurah Yudha Martin Mahardika (Jurnal Manajemen Perhotelan dan Pariwisata, 2026)
This study aims to examine the implementation of green tourism experiences at Sanggraloka Farm, Bresela Village, Gianyar, and describe tourist perceptions and identify challenges and opportunities in developing sustainable tourism. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that Sanggraloka Farm implements the concept of green tourism through environmental conservation, nature-based educational activities, environmentally friendly facilities, and active involvement of the local community. Tourist perceptions of green tourism experiences are very positive, especially regarding aspects of natural authenticity, direct involvement in agricultural activities, and comfort of facilities. Challenges faced include managing human resources and road access, while opportunities lie in strengthening environmental education, the development of a butterfly park and empowering the local community. This study has implications for the importance of integrating green tourism experiences in developing sustainable destinations.